2015 IEEE Global Communications Conference (GLOBECOM) 2014
DOI: 10.1109/glocom.2014.7417347
|View full text |Cite
|
Sign up to set email alerts
|

Joint Power Splitting and Secure Beamforming Design in the Wireless-Powered Untrusted Relay Networks

Abstract: Abstract-In this work, we maximize the secrecy rate of the wireless-powered untrusted relay network by jointly designing power splitting (PS) ratio and relay beamforming with the proposed global optimal algorithm (GOA) and local optimal algorithm (LOA). Different from the literature, artificial noise (AN) sent by the destination not only degrades the channel condition of the eavesdropper to improve the secrecy rate, but also becomes a new source of energy powering the untrusted relay based on PS. Hence, it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The key idea behind SWIPT is that a wireless node can capture radio‐frequency (RF) signals sent by a source node and then transform them into direct current to charge the node's rechargeable battery to the extent that it further can make use of it for signal processing or information transmission (IT) [14]. In recent years, great efforts have been dedicated to the study of SWIPT for non‐security‐based [15, 16] and security‐based systems [17–26]. Nasir et al .…”
Section: Introductionmentioning
confidence: 99%
“…The key idea behind SWIPT is that a wireless node can capture radio‐frequency (RF) signals sent by a source node and then transform them into direct current to charge the node's rechargeable battery to the extent that it further can make use of it for signal processing or information transmission (IT) [14]. In recent years, great efforts have been dedicated to the study of SWIPT for non‐security‐based [15, 16] and security‐based systems [17–26]. Nasir et al .…”
Section: Introductionmentioning
confidence: 99%
“…We assume that the jamming signal can readily be cancelled off since it is known to the destination. 12,16,17 Secure transmission performance…”
Section: Energy Harvesting and Information Processingmentioning
confidence: 99%
“…A constellation-rotation aided scheme was proposed to avoid information leakage to the untrusted relay and enhance the transmission reliability in Xu et al 15 Recently, some works about untrusted energy harvesting relay networks have been considered in the context of physical layer security. In Zhao et al, 16 using power splitting scheme, the problem of secrecy rate maximization in multiple wireless powered untrusted AF relay networks was investigated. The secrecy outage probability (SOP) between a source and a destination via a energy constrained untrusted node powered by wireless radio frequency signals was studied in Kalamkar and Banerjee.…”
Section: Introductionmentioning
confidence: 99%
“…Untrusted relay channels with confidential messages were first studied in [3], where the intermediate relay acted as both an eavesdropper and a helper. The papers [4][5][6][7] studied the security of the untrusted relay in different scenarios. The paper [4] considered the relay channel with a relay that was an eavesdropper and whether the untrusted relay may help the source and the destination.…”
Section: Introductionmentioning
confidence: 99%
“…In [6], a successive relaying scheme was proposed to secure the AF relaying network with multiple untrusted nodes and it was shown that the scheme could improve the security performance. In addition, secure beamforming with untrusted relay was considered in [7,8].…”
Section: Introductionmentioning
confidence: 99%